Statin use is associated with fewer periodontal lesions: A retrospective study - Mäkelä Marja; Suomalainen Kimmo; Lindy Otso; Lindy Seppo (BMC, 2008)
Abstract Background Inflammatory processes are considered to participate in the development of cardiovascular disease (CVD). Statins have been used successfully in the prevention and treatment of coronary heart disease. Chronic periodontitis has been suggested to contribute to CVD. The aim of this study was to examine the association of statin use and clinical markers of chronic periodontitis. Methods Periodontal probing pocket depth (PPD) values were collected from dental records of 100 consecutive adult patients referred to a university dental clinic for treatment of advanced chronic periodontitis. A novel index, Periodontal Inflammatory Burden Index (PIBI), was derived from the PPD values to estimate systemic effects of periodontitis. Results Periodontitis patients taking statins had a 37% lower number of pathological periodontal pockets than those without statin medication (P = 0.00043). PIBI, which combines and unifies the data on PPD, was 40% smaller in statin using patients than in patients without statin (P = 0.00069). PIBI of subjects on simvastatin and atorvastatin both differed significantly from patients without statin and were on the same level. The subjects' number of teeth had no effect on the results Conclusion Patients on statin medication exhibit fewer signs of periodontal inflammatory injury than subjects without the statin regimen. PIBI provides a tool for monitoring inflammatory load of chronic periodontitis. The apparent beneficial effects of statins may in part be mediated by their pleiotropic anti-inflammatory effect on periodontal tissue.